Experimentation proposal for teaching physics and biological science - Oliveira do Nascimento, Elaine; Maria dos Santos Lobato Junior, José; Maia de Jesus Chaves Neto, Antonio; Diego Feitosa de Souza, Francisco; Alessandra Araújo Gonçalves, Maria; Nonato Vieira de Oliveira, Raimundo; Rodrigues Gomes, Daniele; Carlos Matos de Sousa, Jean; Francisco da Silva Costa, José (Seven Editora, 2023)
This article aims to emphasize experimental proposals for the teaching of Physics and Biological Science in Basic Education, considering that the teacher develops the contents by analyzing the contextualization and experimental activities that elucidate explanations of phenomena observed in everyday life. The reason for carrying out such experiments is to approach and deepen the content, to motivate and arouse interest in the aforementioned disciplines. The connection between science, nature and natural phenomena can contribute to scientific knowledge and for this to be possible, the teacher can elaborate situations of observed phenomena, such as the formation of rainbows, drying clothes on the clothesline, formation of mirages on the road, the formation of images in front of mirrors and their applications in the dental area and in commercial establishments, the phases of matter and its phase changes, the appearance of fungi, how to carry out a selective garbage collection, among countless others experiments that you can build to achieve better quality. All these applications that the teacher can use in the contents of Physics and Biological Science, as a result, seek a better compression of certain contents linked to these disciplines. The article concludes considering that the teaching and learning process will bring the student closer to the phenomena he observes in his daily life, which, consequently, constitutes an effective teaching transmitted by the teacher and thus contribute to better learning and at the same time bring closer the everyday student from the application of contextualization and experimental activity. DOI: https://doi.org/10.56238/tfisdwv1-093